Kiai Leadership in Pesantren Political Education: A Historical Study of the Thought of KH. Yusuf Hasyim - Laili Agustinaning Galuh Muninggar; Imam Sukardi (Journal Of Islamic Education And Pesantren, 2024)
Islamic boarding schools (pesantren) play a strategic role in shaping social and political consciousness through the moral and spiritual leadership of the kiai. Nevertheless, political education in pesantren is often narrowly understood as a normative activity or even perceived as incompatible with the neutrality of religious education. This article examines kiai leadership in pesantren-based political education through a historical–intellectual analysis of KH. Yusuf Hasyim’s thought and practice at Pesantren Tebuireng. Employing a qualitative approach, this study combines historical research with library-based inquiry informed by field-based reflection. The data are drawn from historical documents, written works, speeches, archival sources, and reflective accounts of santri experiences, and are analyzed through historical–qualitative interpretation using source and theoretical triangulation. The findings reveal that political education under KH. Yusuf Hasyim was not implemented through formal curricula or ideological indoctrination, but was embedded in moral exemplarity, social–political engagement grounded in Islamic values, and the habituation of civic attitudes within pesantren life. Political education thus operated as a value-based process of political socialization that cultivated moral courage, civic responsibility, and national consciousness among santri. This study argues that kiai leadership in pesantren constitutes a distinctive model of ethical and contextual Islamic political education, offering a significant contribution to contemporary discussions on leadership, Islamic education, and civic formation in plural societies.